MEMBENTUK KARAKTER ROHANI PESERTA DIDIK MELALUI MEDIA PEMBELAJARAN PASTORAL - Purwanto, Martinus Hary; Tarihoran, Emeria (Bahasa Indonesia, 2025)
Spiritual character education is a crucial aspect of holistic education for Christian students. Pastoral learning media can be an effective means of cultivating spiritual character. These media are designed to help students know God, love others, and develop their potential based on Christian values. This article aims to explain how pastoral learning media can be utilized as a tool to shape the spiritual character of Christian students. Pastoral learning media encompasses various forms such as books, videos, audio, songs, drama, and other media that suit the context and needs of students. The methodology used in this article is a literature review that examines the principles of designing, implementing, and evaluating pastoral learning media. The article also outlines practical steps in the design, implementation, and evaluation of these media. It is hoped that this article will contribute significantly to the development of spiritual character education in Christian schools and colleges. By utilizing appropriate pastoral learning media, Christian students can be prepared to become individuals of strong faith, noble character, and ready to serve the church and nation.